2021
DOI: 10.5194/hess-25-6333-2021
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “A comparison of catchment travel times and storage deduced from deuterium and tritium tracers using StorAge Selection functions” by Rodriguez et al. (2021)

Abstract: Abstract. The combined use of deuterium and tritium to determine travel time distributions (TTDs) in streams is an important development in catchment hydrology (Rodriguez et al., 2021). This comment takes issue with Rodriguez et al.'s assertion that the truncation hypothesis may not hold for catchments in general, i.e. that the use of stable isotopes alone may not lead to underestimation of travel times or storage compared to tritium. We discuss reasons why the truncation hypothesis may not appear to hold for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The specific magnitude of such a water age threshold remains difficult to quantify with the available data. However, given the results in the Neckar study basin, the question raised by Stewart et al (2021), if δ 18 O allows to see "the full range of travel times", can to some extent be answered: it can be assumed that, when used with a suitable model, δ 18 O contains sufficient information for a meaningful characterization of water ages in systems characterized by MTTs of at least ~15 -20 years, which encompasses the vast majority of river basins so far analyzed in literature (see Stewart et al, 2010 and references therein). As a step forward, the original hypothesis above can, for future research, be reformulated into: δ 18 O-inferred water age estimates are subject to increasing uncertainty and bias when compared to 3 H-inferred estimates when stream water MTTs of ~ 15 -20 years are exceeded in systems characterized by increasingly old water.…”
Section: The Individual Roles Of the Choices Of Tracers And Models Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The specific magnitude of such a water age threshold remains difficult to quantify with the available data. However, given the results in the Neckar study basin, the question raised by Stewart et al (2021), if δ 18 O allows to see "the full range of travel times", can to some extent be answered: it can be assumed that, when used with a suitable model, δ 18 O contains sufficient information for a meaningful characterization of water ages in systems characterized by MTTs of at least ~15 -20 years, which encompasses the vast majority of river basins so far analyzed in literature (see Stewart et al, 2010 and references therein). As a step forward, the original hypothesis above can, for future research, be reformulated into: δ 18 O-inferred water age estimates are subject to increasing uncertainty and bias when compared to 3 H-inferred estimates when stream water MTTs of ~ 15 -20 years are exceeded in systems characterized by increasingly old water.…”
Section: The Individual Roles Of the Choices Of Tracers And Models Fo...mentioning
confidence: 99%
“…The authors concluded that these results cast some doubt on "[…] the perception that stable isotopes systematically truncate the tails of TTDs" (Rodriguez et al, 2021). However, their interpretation was questioned by Stewart et al (2021), who pointed out that simply no older water may be present in their study catchment.…”
Section: Introductionmentioning
confidence: 98%
“…Present-day tritium activities in precipitation have recovered natural cosmogenic levels, i.e., similar to levels noted before the nuclear tests (Cauquoin et al, 2015;Terzer-Wassmuth et al, 2022). However, bomb tritium remains present in the hydrological cycle of the earth (Stewart et al, 2021). The interest in tritium water dating has recently gained new momentum (Morgenstern et al, 2010;Stewart et al, 2012).…”
mentioning
confidence: 57%
“…allowed first to carry out explicit water transit time analyses for several years past the mid-1960's bomb peak, the latter acting as a clear time marker. With the bomb tritium pulse decay observed after the 1970's, tritium dating of hydrological systems had to increasingly rely on time series with several measurements to deliver unambiguous results -eventually leading to a fading interest in tritium as a tracer of choice for water age dating (Stewart and Morgenstern, 2016;Stewart et al, 2021).…”
mentioning
confidence: 99%
“…We point out that, in New Zealand and the Southern Hemisphere in general, bomb tritium has now fully dispersed, removing any ambiguity from fitting LPMs and increasing the reliability of tritium-based age interpretations. This is not yet the case for the 225 Northern Hemisphere, where bomb tritium is still present in significant amounts within the groundwater systems still causing ambiguity in the age interpretations (Stewart et al, 2021).…”
Section: Datamentioning
confidence: 99%